122k views
5 votes
Giovanni justifies whether the expression -4x-8 is equivalent to -2(x+1)-2(x+3) by letting x=3 in both expressions. What is the value of each expression when x=3.

3 and -20
4 and 4
-20 and -20
3 and 4

User Shavaughn
by
5.7k points

1 Answer

5 votes

Answer:

The value of each expression when x=3 will be -20 and -20.

Explanation:

Given the expression

-4x-8

setting x=3

= -4(3)-8

=-12-8

=-20

Given the expression

-2(x+1)-2(x+3)

setting x=3

=-2(3+1)-2(3+3)

=-2(4)-2(6)

=-8-12

=-20

so we conclude that the value of both the expressions was -20 when we substituted the value x=3.

Therefore, the value of each expression when x=3 will be -20 and -20.

User Tahjid Ashfaque
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.